2004
DOI: 10.1111/j.1365-2265.2004.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged fasting and postprandial adiponectin levels following a 4‐day caloric restriction in young healthy men

Abstract: Fasting and postprandial adiponectin levels are not acutely modulated by a short-term energy restriction in young healthy men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
5
26
1
2
Order By: Relevance
“…The unchanged plasma adiponectin in R cows compared with the C cows indicates that its circulating concentration is not affected by energy balance. The finding of unchanged adiponectin concentrations during feed restriction agrees with results of energy restriction (4 d) study in humans (Imbeault et al, 2004) and total feed deprivation studies in rodents (48 h of fasting; Combs et al, 2003;Kmiec et al, 2005) and humans (48 to 72 h of fasting; Gavrila et al, 2003;Merl et al, 2005). However, another report suggests that adiponectin concentration is decreased in mice after 8 h of fasting (Gui et al, 2003).…”
supporting
confidence: 78%
“…The unchanged plasma adiponectin in R cows compared with the C cows indicates that its circulating concentration is not affected by energy balance. The finding of unchanged adiponectin concentrations during feed restriction agrees with results of energy restriction (4 d) study in humans (Imbeault et al, 2004) and total feed deprivation studies in rodents (48 h of fasting; Combs et al, 2003;Kmiec et al, 2005) and humans (48 to 72 h of fasting; Gavrila et al, 2003;Merl et al, 2005). However, another report suggests that adiponectin concentration is decreased in mice after 8 h of fasting (Gui et al, 2003).…”
supporting
confidence: 78%
“…We were interested in determining whether adiponectin decreased during fasting and whether a change in adiponectin promoted alterations in insulin action. Others have reported that 4 days of caloric restriction (25) or 72 h of fasting (6) did not change basal adiponectin concentration in lean men. Similarly, we found that basal adiponectin concentration did not change with 48 h of fasting in lean men and women (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…95 In men, similarly, adiponectin levels were unchanged following consumption of an 800 kcal/day diet for four days. 96 We have observed a modest (ϳ10%) but significant increase in serum adiponectin in normal-weight women following consumption of a calorie-restricted (600 kcal/day) diet for one week; interestingly, the opposite effect (an ϳ20% decrease of adiponectin) was observed in men restricted to 800 kcal/day. 97 One study of healthy normal-weight women restricted to 1000 to 1200 kcal/day for four weeks showed a significant reduction in adiponectin concentrations (16%), despite an average weight loss of 3.4 kg.…”
Section: Effects Of Caloric Restriction and Weight Loss On Circulatinmentioning
confidence: 93%